Legal Analysis of Represive Actions of The Polri in Facing Demonstrations in The City of Bima - Irawansah, Didik; Ridwan; Kasmar; Muhammad Amin (Universitas Muhammadiyah Bima, 2024)
Repressive actions against demonstrators have become hot news among the public. This action is considered a form of violence against demonstrators and is considered not in accordance with Standard Operating Procedures (SOP) in security and order. This article aims first, to describe the form of repressive police action against demonstrations in Bima City secondly, describing the Authority of the Indonesian National Police in Handling Demonstrations. Empirical Legal Research Methods, socio-legal approach, data collection through interviews and documentation and drawing narrative conclusions. The results of the research show: Security measures taken by the Bima City Police were found in several demonstrations which were deemed to disrupt security or public order with various procedures and standards regulated according to statutory regulations. public, destruction of facilities, throwing stones and/or disturbing other public order security, however the actions taken by the police are measurable and standardized while in terms of regulations, this form of security and order action refers to the Regulation of the Chief of Police of the Republic of Indonesia Number 7 of 2012 and National Police Regulation Number 16 of 2006 concerning Crowd Control.